All the World's Entrepreneurs: The Role of Self-Employment in Nineteen Nations - Dennis Hal Sullivan; Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1997)
The purpose of this paper is to describe the effect of self-employment income on the distribution of market income among households in nineteen nations. Many of the nations are high-income OECD countries, but we also include several countries with lower levels of income per capita, including four formerly Communist countries. As this stage, our study is exploratory and descriptive: we find several stylized patterns in the distributive effects of self-employment, some of which suggest testable hypotheses to be examined in subsequent work.
Keywords: 330; Selbstständige; Einkommensverteilung; OECD-Staaten; Osteuropa